Assessment of chain-of-custody certification costs for sawnwood manufacturers in Peninsular Malaysia - A. G., Nor Suryani; Othman, Mohd Shahwahid; Puasa, Ahmad Fauzi; Radam, Alias; R. P., Vlosky (Forest Research Institute Malaysia, 2011)
In response to environmental concerns, over the past two decades, many environmental organisations, government entities, wood product manufacturers and other companies in wood products supply chains have developed standards to encourage consumers to purchase wood originating from certified sustainable forests. This paper focuses on the chain-of-custody (CoC) component of certification. A study involving sawnwood manufacturers in Malaysia was conducted to determine an accurate cost of obtaining a Malaysian Timber Certification Council (MTCC) CoC certificate. There are three types of costs to obtain a MTCC–CoC certificate: (1) cost to meet CoC standard or requirement (an indirect cost), (2) auditing cost (a direct cost) and (3) surveillance visit cost (a direct cost). Results indicated that the cost to meet CoC standard is the major component involving 96% of the total cost of certification, whereas the auditing and surveillance visit each only involved 2% of the total certification cost. None of the three CoC costs were statistically correlated with company size (as measured by annual sales) but there was a statistically significant relationship between cost of surveillance visit and company size when measured by annual production.